ASSOCIATION OF FEBRILE SEIZURES AND IRON DEFECIENCY ANEMIA - Tahir Mahmood; Nasir Khan sajjid; Fida Muhammad (Journal of University Medical & Dental College, 2017)
ABSTRACT: BACKGROUND: Febrile seizures (FS) aﬀect 3-4% of children under the age of 5 years. It is benign and has an excellent prognosis. Male children with family history of febrile seizures, low serum calcium, sodium & blood sugar and microcytic hypochromic anemia are more prone to FS. Iron deﬁciency has been postulated to contribute to FS as it has a key role in brain energy metabolism, myelination, long term behavioral changes and cognitive impairments. PATIENTS AND METHODS: A case-control study was conducted in the Department of Pediatrics Allied Hospital, Faisalabad from December 2014 to November 2015. Forty ﬁve children with fever and seizures and 45 children with fever but no seizure, of age 6 months to 60 months, were recruited. Blood samples of the children were obtained. Serum ferritin and Mean Corpuscular Volume (MCV) levels were assessed. Iron deﬁciency was labeled at Serum ferritin <7 μg/L and MCV <65 fL. Data was entered and analyzed using SPSS v. 20.0. RESULTS: 60% (n=27) of children with febrile seizures showed iron deﬁciency anemia out of which 59% (n=16) were males and 41% (n=11) were females and most of these children 48% (n=13) belonged to the age group of 13 to 30 months. Logistic regression analysis and p value showed iron deﬁciency to be signiﬁcantly associated with febrile seizures. Odds ratio showed children with febrile seizures to be 6.93 times more prone to develop iron deﬁciency. CONCLUSION: Febrile seizures are signiﬁcantly associated with iron deﬁciency and the children with iron deﬁciency has about 6 times more chances of developing febrile seizures as compared to children with normal serum ferritin levels.